Mapping Civic Literacy Research: An Integrated Systematic Review and Bibliometric Analysis - Ridha, Muhammad Kamil; Arpannudin, Iqbal; Ma'rifatun, Rizqi; Haryanto, Yudhi (Universitas Negeri Semarang, 2025)
This study maps the scholarly landscape of civic literacy through an integrated systematic review and bibliometric analysis. Using Scopus (search date: September, 16, 2025; coverage 1980–2025), we screened records via PRISMA and analyzed the final corpus with VOSviewer to identify publication trends, collaboration networks, and keyword co-occurrences. Results show a pronounced growth of civic literacy publications since the late 2000s, with the United States as the dominant contributor and Indonesia emerging as a notable node. Co-occurrence analysis reveals four interconnected clusters: (1) schooling and digital engagement (citizenship education, social media, misinformation); (2) democratic concerns and global issues; (3) public health and gender; and (4) creative/arts-based education. Collaboration networks remain relatively sparse, indicating opportunities to strengthen cross-national partnerships and diversify methodological approaches. The review highlights civic literacy as a transdisciplinary construct that links political knowledge, digital/media competencies, and participatory practices, and underscores the implications for curriculum design, teacher education, and policy, particullary the integration of digital literacy to meet the challenges of Society 5.0. We conclude that future research should deepen interdisciplinary integration, expand international collaboration, and develop context-responsive models for civic literacy in schools and communities.